High frequency wind energy conversion system for offshore DC collection grid—Part I: Comparative loss evaluation. (March 2016) - Agheb, Edris; Holtsmark, Nathalie; Høidalen, Hans K.; Molinas, Marta
Abstract: In this paper, the investigation of an offshore wind energy conversion system with a high frequency link is continued. The design of the conversion system aims for a high efficiency and low weight and volume. It is composed of a permanent magnet generator, an AC–AC converter, a high frequency transformer and a diode bridge rectifier. The system is intended for a DC collection grid of turbines connected in series. Three different AC–AC converters are considered: the direct and indirect matrix converter and the back-to-back converter. The design of the entire conversion system is presented with emphasis on the converter and the high frequency transformer. The efficiencies of these two components as well as filters are assessed using a simulation model of the conversion system and device datasheet for the converter and analytical analysis for the transformer and filters. The conversion systems with the three converters show comparable efficiency performance; the system with the matrix converter however displaying the highest efficiency of 96.53 %, the indirect matrix converter 86.4 % and the back-to-back the lowest, 96.36 % or 93.51 % depending on the filter design. This paper is the prequel to a second part where the conversion system is further developed to improve the converter efficiency and the transformer design.